The Current Carriers’ Dispersion Law of a Crystal, Their Chemical Potential and a Set of Important Properties of Crystals - Budzhak, Ya. S.; Wacławski, T. (Physics and Chemistry of Solid State, 2020)
In this paper, a new non-parabolic dispersion law has been established, which for a small parameter of the spectrum nonparabolicity coincides with the known Kane’s nonparabolic dispersion law. The Kane’s dispersion law works well when the well-known parameter of nonparabolicity is much less than 1, and the new law works well enough when the parameter of nonparabolicity is less than 1. In addition, this law shows that crystals with a band gap (i.e., forbidden band width) Eg 10-1 eV – these are semiconductor crystals, crystals with Eg 10-2 eV – these are metals.